(untitled) (The Journal of Psychology and Sociology, 2017)
On the social character of young scientists greatly affects important components of the mismatch of their authority such as a professional strategy, productivity and level of professional education. Sociology is the basis for the formation of scientific, technical, social and human resources, policy which is based on the results of research in this field. In many cases, revealed a lack of monitoring of sociological studies that address the social problems of young people engaged in research work such as a desire to choose a career in science, the value of scientific activity and the impact of its rules, the social obstacles to the implementation of the scientific sphere, the development of professional skills and others. The institutional view of young scientists makes it possible to consider from the perspective of social institutions, the social authority of socio-professional group. The analysis revealed some modernization mutually opposite sides of the formation of the educational activities of this group in higher education and training of highly qualified researchers in the modern labor market conditions. Actual problems of modernization of the scientific and scientific-pedagogical staff in higher education are: the election of best model of cultivation in today’s new research culture, capricious freedom in thinking, creativity, innovation. This article discusses issues that make it possible to analyze the problems and processes of high school, and domestic science in the social and professional system, to determine the possibility of a social group that is to establish their social status. In connection with this very extensively considered question regarding the status of the scientific institution and employment problems of Kazakhstan’s society. The main method of research of professional groups is a socio-structural method, examines the social and professional structure as part of the social structure of society. Socio-structural method when considering the scientific staff that anticipates social and professional quality of the scientific community, the mechanisms of mobility including study of continuous modern intellectual education. Key words: science, scientific activity, youth, young scientists, motivation.